Social media for environmental sustainability awareness in higher education. Issue 4 (2nd May 2017) - Hamid, Suraya; Ijab, Mohamad Taha; Sulaiman, Hidayah; Md. Anwar, Rina; Norman, Azah Anir
Abstract : Purpose: The explosion of social media use such as Facebook among higher education students is deemed to have great potential in widely disseminating environmental sustainability awareness. The paper aims to capture, summarise, synthesise and comment on the role of social media to garner interest of students and staff on environmental sustainability issues. Design/methodology/approach: Systematic literature review technique is adopted, and three selected online databases were searched for relevant papers for review. Specific data were extracted from each paper, and the discussion section was based on the developed research questions. Findings: Higher education needs to fully leverage the ubiquity of social media to extend how environmental sustainability is viewed by the students and staff. Sustainability practices conducted at the university level such as recycling, reduction of electricity and water consumptions and paper reduction in classroom and used to engage students on environmental matters. For staff, social media can be leveraged as to convey the university policy and assist in their quest to become full-fledged green universities. Research limitations/implications: Some of the limitations of this research include the lack of keyword search using synonyms or related terms equivalent to the term "awareness", lack of forward and backward searches, and the papers were searched until end of 2013 only. Future research needs to take advantage of the current limitations to investigate this topic and be empirically supported by theories using quantitative, qualitative or mixed-method-based research. Future studies could also develop relevant frameworks to propose an effective use of social media for creating environmental sustainability awareness in higher education. Practical implications: Propagations of environmental sustainability awareness in higher education would be more effective with the use of social media. Social implications: In principle, the increase of environmental awareness level would increase the students' good behavioural conduct on environmental sustainability. Originality/value: While the broad topic of environmental sustainability in higher education is widely discussed, the role of social media in shaping environmental sustainability awareness is still under researched. This situation provides a significant potential for exploration by sustainability researchers to craft their investigation on the effective role of social media in creating environmental awareness in higher education.